CHARACTERISTICS OF AFLATOXIN CONTAMINATION IN MEDICINAL PLANTS AT NGHE AN TRADITIONAL MEDICINE HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and some related factors of aflatoxin contamination in traditional herbal medicines at Nghe An Traditional Medicine Hospital in 2023.Subjects and methods: A sample size of 170 traditional herbal medicines included in the list of medicines covered by insurance was used. The study was a descriptive experimental design conducted in the laboratory using high-performance liquid chromatography for qualitative and quantitative determination of aflatoxin.Results: The overall aflatoxin contamination rate was 16/170, with 9 samples contaminated with one type of aflatoxin, 5 samples contaminated with two types of aflatoxin, and 2 samples contaminated with three types of aflatoxin. There were 25 instances of aflatoxin contamination (14.41%), with the highest rate of aflatoxin B2 contamination (48%), followed by aflatoxin G1 at 24%, aflatoxin B1 at 16%, and the lowest rate of aflatoxin G2 at 12%. The aflatoxin contamination rate in traditional medicine samples contaminated with mold was 19.64%, while in samples not contaminated with mold it was 4.39%. The aflatoxin contamination rate in traditional Chinese medicine (15.73%) was higher than in traditional Vietnamese medicine (2.47%).Conclusion: Aflatoxin contamination in traditional medicine products is cumulative over time due to mold contamination. Therefore, a model for assessing health risks from aflatoxin exposure is needed.
Keywords: Medicinal plants, fungus, aflatoxin.